2008
DOI: 10.1186/1471-2458-8-55
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence against women in rural Vietnam - different socio-demographic factors are associated with different forms of violence: Need for new intervention guidelines?

Abstract: Background: This population-based study investigated the different forms, magnitude and risk factors of men's violence against women in intimate relationships in a rural part of northern Vietnam and whether a difference in risk factors were at hand for the different forms of violence. Vietnam has undergone a rapid transition in the last 20 years, moving towards a more equal situation for men and women however, Confucian doctrine is still strong and little is known about men's violence against women within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
65
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 21 publications
16
65
3
Order By: Relevance
“…As was the case for eight of our nine individual interview participants, post-marital patrilocal residence dominates in Vietnam, and women thus live in households where their in-laws are heads (Rydström 2010). Our informants, however, did not mention intimate partner violence as a reason for their distress, though lifetime prevalence rates of violence in the present study setting have been found to be as high as 31 % (Nguyen et al 2008) and it has been implicated in the causation of perinatal depression (Edhborg et al 2011). This lack of discussion may have been influenced by the strong cultural tradition of not revealing what is going on within the family (Jonzon et al 2007).…”
Section: Discussionmentioning
confidence: 65%
“…As was the case for eight of our nine individual interview participants, post-marital patrilocal residence dominates in Vietnam, and women thus live in households where their in-laws are heads (Rydström 2010). Our informants, however, did not mention intimate partner violence as a reason for their distress, though lifetime prevalence rates of violence in the present study setting have been found to be as high as 31 % (Nguyen et al 2008) and it has been implicated in the causation of perinatal depression (Edhborg et al 2011). This lack of discussion may have been influenced by the strong cultural tradition of not revealing what is going on within the family (Jonzon et al 2007).…”
Section: Discussionmentioning
confidence: 65%
“…15e17 While medical schools in the USA often include IPV education, 18 to the best of the authors' knowledge, there are no formal IPV curricula at medical schools in Vietnam and China. Studies in Vietnam, 16 China 19 and the USA 15,20,21 have shown that IPV victims are more likely to be diagnosed with injuries, chronic pain syndromes, mental health problems, reproductive health issues, cardiovascular disease and poorer health overall than individuals who have never experienced IPV. Educating future physicians about the health effects of IPV is essential to improve their skills in addressing this important healthcare issue for women.…”
Section: Introductionmentioning
confidence: 99%
“…physical, emotional, and sexual). A study conducted with married women in Vietnam reported the proportion of women exposed to both physical and sexual violence as 32.7% (Vung, Ostergren, & Krantz, 2008). In our study, more than half of the participants reported at least one of the behaviors involving sexual violence in their current marriages by their husbands (Table 2).…”
Section: Discussionmentioning
confidence: 50%